The TrkB‐T1 receptor mediates BDNF‐induced migration of aged cardiac microvascular endothelial cells by recruiting Willin. Issue 2 (22nd January 2019) - Wang, Zhefeng; Chen, Yilin; Chen, Xuwei; Zheng, Xin; Xu, Ganlin; Yuan, Ziqiang; Zhao, Hui; Chen, Wensheng; Li, Lilin; Zheng, Nianjue; Shen, Xiaotao; Li, Yanmei; et al.
Abstract: The mechanism of age‐related decline in the angiogenic potential of the myocardium is not yet fully understood. Our previous report revealed that the aging of cardiac microvascular endothelial cells (CMECs) led to changes in their expression of receptor Trk isoforms: among the three isoforms (TrkB‐FL, TrkB‐T1 and TrkB‐T2), only the truncated TrkB‐T1 isoform continued to be expressed in aged CMECs, which led to decreased migration of CMECs in aging hearts. Thus far, how BDNF induces signalling through the truncated TrkB‐T1 isoform in aged CMECs remains unclear. Here, we first demonstrated that aged CMECs utilize BDNF–TrkB‐T1 signalling to recruit Willin as a downstream effector to further activate the Hippo pathway, which then promotes migration. These findings suggest that the aging process shifts the phenotype of aged CMECs that express TrkB‐T1 receptors by transducing BDNF signals via the BDNF–TrkB‐T1–Willin–Hippo pathway and that this change might be an important mechanism and therapeutic target of the dysfunctional cardiac angiogenesis observed in aged hearts.